Water Treatment Technology (Laboratory) - Mimi Suliza Muhamad (2023)
This book presents the hands-on activities on experimental works related to water treatment process of a drinkable pilot plant that can be performed by students from Bachelor of Civil Engineering Technology (Environment), UTHM. Each chapter present different experimental works that is conducted in sequence (for chapter one until six) as in real water treatment plant using a drinkable pilot plant. First chapter is on coagulation and flocculation process. Followed by second chapter which is sedimentation process. The third chapter is about sand and carbon filtration process while the fourth chapter is on chlorination and fluoridation process. In chapter five is about ultrafiltration membrane and ultraviolet sterilization process. After the treatment processes, chapter six present on slurry dewatering process. Chapter seven is about reverse osmosis process which is conducted using an RO unit for the experiment of membrane resistance and salt rejection.